Adverse drug reactions in hospitalised cardiac patients: risk factors - Mugoša, Snežana (Vojnosanitetski pregled, 2015)
Introduction/aim: Adverse drug reactions (ADRs) appear more frequently then actually reported and registered. The main goal is to analyze occurrence and characteristics of ADRs.Methods: We performed prospective study with 200 patients included, hospitalized at Cardiology Centre, Clinical Centre of Montenegro. ADRs were collected using special designed questionnaire, based on the symptoms’ lists and any signs that could point to eventual ADRs. Data from patients’ medical charts, lab tests and other available parameters were observed and combined with the data from questionnaire. Severity of ADRs was assessed according to World Health Organization criteria as serious and non serious ADRs. Causality was assessed using Naranjo probability scale.Results: Of all patients, 34% experienced at least one of ADRs. The most common ADRs occurred as nervous system disorders, than cardiovascular disorders, and the less frequent were immune system disorders. Serious ADRs occurred at 16% of all detected, caused by carvedilol and amiodarone. The majority of patients (97,3%) recovered without consequences. The multivariate analysis showed several independent significant associations between ADRs and age, gender, co-morbidities and polypragmasia.Conclusion: ADRs represent a significant issue in hospitalized cardiac patients population. The most significant predictors for ADRs occurred in observed population were age, co-morbidity, number of medications used during hospitalization and patients’ gender. Bringing preventive measures out for patients exposed to detected risk factors, like pharmacotherapy rationalization and additional education of health professionals, could minimize the frequency of ADRs. Key words: adverse drug reactions, intensive monitoring, pharmacovigilance